A large enhancement of magnetocaloric effect by chemical ordering in manganites. Issue 5 (22nd January 2018) - Wang, Yanmei; Zhu, Yinyan; Liu, Hao; Lin, Hanxuan; Miao, Tian; Yu, Yang; Han, Furong; Wang, Wenbin; Sun, Jirong; Yin, Lifeng; Shen, Jian
Abstract : A dramatic enhancement of magnetocaloric effect by controlling the length scale of electronic phase separation in manganite films. Abstract : For conventional ferromagnetic systems, the magnetocaloric effect (MCE) is dominated by the entropy changes upon magnetic phase transitions. For strongly correlated oxides such as manganites, in which competing magnetic orders coexist and respond to an external field differently, the MCE is more complex due to the electronic phase separation (EPS) phenomenon. Taking the well-known (La2/3 Pr1/3 )5/8 Ca3/8 MnO3 (LPCMO) manganite as a model system, we investigated how the length scale of EPS phases affects the MCE. Specifically, the EPS length scale can be dramatically reduced by the spatial ordering of Pr dopants in the LPCMO system. Experimental results indicate that the magnetic entropy change of the Pr-ordered LPCMO is considerably larger than that of the Pr-random LPCMO by a factor up to six at the onset temperature of the ferromagnetic phase. A direct relation between the length scale of EPS and MCE has been established based on the experimental results.